Influence 0f Halal Culture and Literacy on The Interest of Saving The People of Tobelo City In Islamic BANKS - Abdul Rauf Wajo; Saiful Saiful; Nurfadila Conoras (IAIN Ternate, 2021)
The study aimed to find out the influence of halal culture and literacy on the saving interests of tobelo city people in Islamic banks, using a sample of 100 people randomly obtained in the city of Tobelo. The data used in this study is primary data obtained by way of in-person interviews on the ground. and to influence the influence of halal culture and literacy on the interests of saving the people of Tobelo city in Sharia banks, used multiple linear regression analysis with SPSS 20 tools. From the results of the hypothesis test, it is seen that cultural variables have no effect on people's saving interest in Tobelo city towards Islamic banks. This is evidenced by testing the significant value for the effect of X1 on Y is 0.903 > 0.05 and the value of t calculated 0.122 < t table 2.577 so it can be concluded that H1 is rejected which means there is no effect of X1 on Y. While the Halal Literacy Variable is very influential on the interest in saving the People of Tobelo City in Sharia Bank. Keywords: Culture, Halal Literacy, Ask to save, Sharia Bank